Against Crime In The Green Hornet Movie Directed ByMichel Gondry (2011): A Sociological Approach - Cahyono, Wahyu Andi (2012)
The research is aimed to know the effort of Against Crime in The Green Hornet movie by using sociological approach. The objective of this study is to analyze the movie based on the structural elements and to analyze the movie based on the sociological approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is The Green Hornet movie directed by Michel Gondry (2011). While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en scene, cinematography, sound, and editing are related to each other and form the unity into good quality movie. Second, based on the sociological analysis, there is relation between this movie and the social reality in America in early twenty first century. The Green Hornet movie shows what happened behind the life politics in America and people who fight against politics crime.